2008
DOI: 10.1002/cphc.200800475
|View full text |Cite
|
Sign up to set email alerts
|

A DFT‐Based Investigation of Hydrogen Abstraction Reactions from Methylated Polycyclic Aromatic Hydrocarbons

Abstract: The growth of polycyclic aromatic hydrocarbons (PAHs) is in many areas of combustion and pyrolysis of hydrocarbons an inconvenient side effect that warrants an extensive investigation of the underlying reaction mechanism, which is known to be a cascade of radical reactions. Herein, the focus lies on one of the key reaction classes within the coke formation process: hydrogen abstraction reactions induced by a methyl radical from methylated benzenoid species. It has been shown previously that hydrogen abstractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 87 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…[65] Tunneling corrections were not included, since it was previously shown that Eckart tunneling refinements lead to a decrease of approximately 5 kJ mol À1 in activation energies of hydrogen abstraction reactions from hydrocarbons. [19,25,26] This decrease is negligible compared to the difference in activation energies between hydrogen abstraction and addition reactions, as will be shown below. Reaction rate coefficients were calculated in the temperature range 700-1100 K, which is characteristic for thermal cracking (see Supporting Information), and kinetic parameters were estimated by fitting the Arrhenius equation to these data.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…[65] Tunneling corrections were not included, since it was previously shown that Eckart tunneling refinements lead to a decrease of approximately 5 kJ mol À1 in activation energies of hydrogen abstraction reactions from hydrocarbons. [19,25,26] This decrease is negligible compared to the difference in activation energies between hydrogen abstraction and addition reactions, as will be shown below. Reaction rate coefficients were calculated in the temperature range 700-1100 K, which is characteristic for thermal cracking (see Supporting Information), and kinetic parameters were estimated by fitting the Arrhenius equation to these data.…”
Section: Methodsmentioning
confidence: 84%
“…The intrinsic reaction coordinate (IRC) [55,56] paths were traced to find the two associated minima directly connected to each transition state (TS) on the potential-energy surfaces. The BMK [57] functional, particularly developed for kinetics and well-known for its good performance in both radical and nucleophilic substitution reactions, [19,25,27,39,58] was employed in conjunction with the 6-311 + GA C H T U N G T R E N N U N G (3df,2p) basis set to further refine energies of B3LYP optimized structures. The BMK/6-311 + G-A C H T U N G T R E N N U N G (3df,2p)//B3LYP/6-31 + GA C H T U N G T R E N N U N G (d,p) level of theory was recently shown to effectively reproduce experimental heats of formation and thermochemical data in reactions of organophosphorus compounds and derived radicals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] Our interest stems from their importance as key intermediates in the coke formation process during steam cracking. [17][18][19][20][21][22][23][24] In particular, we have used various polyaromatic structures to model the coke surface and to study carbon-hydrogen bond dissociation properties and corresponding hydrogen abstraction reactions from both pure and methylated PAHs.…”
Section: Introductionmentioning
confidence: 99%